Photon Conversion and Radiation Synergism in Eu/Tb Complexes Incorporated Poly Methyl Methacrylate - P. Xiao; J. J. Zhang; Z. Q. Wang; H. Lin (Advances in Materials Science and Engineering)
Green and red emissions in terbium and europium benzoic acids (TBA and EBA) incorporated poly methyl methacrylates (PMMA) are exhibited. Larger intensity parameters Ω2 (11.13×10-20 cm2) and Ω4 (13.15×10-20 cm2) of Eu3+ indicate a high inversion asymmetrical and strong covalent environment around lanthanide (Ln) ions and maximum emission cross section σem-max (2.45×10-21 cm2) for the dominant transition D50→F27 of Eu3+ reveals the effective photon conversion capacity in EBA incorporated PMMA. Color variation and fluorescence enhancement are validated to be originated from energy transfer and synergistic effect in TBA/EBA coincorporated PMMA system. The results indicate that Eu and Tb complexes incorporated PMMA with effective photon conversion hold great prospect in increment of lighting quality and enhancement of solar-cell efficiency employed in outer space.